Hormone-free vs. follicle-stimulating hormone–primed infertility treatment of women with polycystic ovary syndrome using biphasic in vitro maturation: a randomized controlled trial - Vuong, Lan N.; Ho, Vu N.A.; Le, Anh H.; Nguyen, Nam T.; Pham, Toan D.; Nguyen, Minh H.N.; Le, Ho L.; Le, Tien K.; Ha, Anh N.; Le, Xuyen T.H.; Pham, Huy H.; Tran, Cam T.; et al. (Fertility and sterility, 2025)
To compare oocyte maturation rates and pregnancy outcomes in women with polycystic ovary syndrome (PCOS) undergoing biphasic in vitro maturation (capacitation in vitro maturation [CAPA-IVM]) with vs. without follicle-stimulating hormone (FSH) priming. Randomized, controlled, assessor-blinded trial. Women aged 18–37 years with PCOS and an indication for CAPA-IVM. Participants were randomized (1:1) to undergo CAPA-IVM with or without FSH priming. The FSH priming group had 2 days of FSH injections before oocyte pickup; no FSH was given in the non-FSH group. After CAPA-IVM, day-5 embryos were vitrified for transfer in a subsequent cycle. The primary endpoint was number of matured oocytes. Secondary outcomes included rates of live birth, implantation, clinical pregnancy, ongoing pregnancy, pregnancy complications, obstetric and perinatal complications, and neonatal complications. The number (interquartile range) of matured oocytes did not differ significantly in the non-FSH vs. FSH group (13 [9–18] vs. 14 [7–18]; absolute difference –1 [95% confidence interval –5 to 4]); other oocyte and embryology outcomes did not differ between groups. Rates of ongoing pregnancy and live birth were 38.3% in the non-FSH group and 31.7% in the FSH group (risk ratio for both outcomes: 1.21, 95% confidence interval 0.74–1.98). Maternal complications were infrequent and occurred at a similar rate in the two groups; there were no preterm deliveries before 32 weeks gestation. These findings open the possibility of a new, hormone-free approach to infertility treatment of women with PCOS. NCT05600972. Tratamiento de infertilidad sin uso de hormonas vs. preparado de hormona folículo estimulante en mujeres con síndrome de ovario poliquístico sometidas a maduración in vitro bifásica: un ensayo controlado aleatorizado Comparar las tasas de maduración de ovocitos y los resultados del embarazo en mujeres con síndrome de ovario poliquístico (SOP) sometidas a maduración in vitro bifásica (maduración in vitro de capacitación [CAPA-IVM]) con y sin preparado de hormona folículo estimulante (FSH). Ensayo aleatorizado, controlado, con evaluador ciego. Hospital privado. Mujeres de 18 a 37 años con SOP e indicación de CAPA-IVM. Las participantes fueron asignadas al azar (1:1) para someterse a CAPA-IVM con o sin preparado de FSH. El grupo con FSH recibió 2 días de inyecciones de FSH antes de la recolección de ovocitos; no se administró FSH en el grupo sin FSH. Después de CAPA-IVM, los embriones del día 5 fueron vitrificados para su transferencia en un ciclo posterior. El criterio de valoración principal fue el número de ovocitos maduros.Los resultados secundarios incluyeron tasas de nacimientos vivos, implantación, embarazo clínico, embarazo en curso, complicaciones del embarazo, complicaciones obstétricas y perinatales, y complicaciones neonatales. El número (rango intercuartil) de ovocitos maduros no difirió significativamente en el grupo sin FSH frente al grupo con FSH (13 [9–18] vs. 14 [7–18]; diferencia absoluta –1 [95 % intervalo de confianza –5 a 4]); Otros resultados de ovocitos y embriología no difirieron entre los grupos. Las tasas de embarazo en curso y nacidos vivos fueron del 38,3% en el grupo sin FSH y del 31,7% en el grupo con FSH (cociente de riesgo para ambos resultados: 1,21; intervalo de confianza del 95%: 0,74 a 1,98). Las complicaciones maternas fueron poco frecuentes y ocurrieron a una tasa similar en los dos grupos; no hubo partos prematuros antes de las 32 semanas de gestación.